AN ANALYSIS OF TEACHER STRATEGIES IN TEACHING WRITING SKILLS IN PANDEMIC ERA (LEARN FROM HOME) - Gani, Siti Nurfadhilah; Munir, Munir; Tahir, Muhammad (PERFORMANCE: JOURNAL OF ENGLISH EDUCATION AND LITERATURE, 2022)
Due to the wide spread of Covid-19, the government started to began online learning activities. This new policies created a new learning environment for students and teacher. This study focused on teacher strategies in teaching writing skills in pandemic era. The aims of this study are to answer the research questions: what are teacher strategies in teaching writing skills during online class and how did the teacher implemented these strategies during online class. This study used qualitative approached. The subject of this study were English Teacher from SMK Negeri 8 Makassar, SMK Negeri 4 Enrekang, and SMA Negeri 5 Enrekang. The research instrument for this study is interview protocol. The result of this study showed that each teacher have a different strategies and how they implemented it. As the interviewed results, these teachers used two strategies, that are Cognitive strategy and Affective strategy. For Cognitive strategy, there are several methods that implemented by the teacher, namely, question and answer, comprehend and understanding, and teaching method. While for the Affective strategy, the method that implemented by teacher is using student’s favourites and experiences as the writing topic.Keywords— Teacher Strategies, Writing Skills, Online Learning.